Optimalisasi Higienitas dengan Sanitary Pontic pada Gigi Tiruan Jembatan Posterior: Laporan Kasus - Muhammad Nasyikhun Amin; Sri Oetami (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Background: Posterior tooth loss can impact masticatory function, aesthetics, and quality of life. Bridges are a restorative solution, but conventional pontic designs often make it difficult to maintain periodontal hygiene and health. Sanitary pontics offer a design that minimizes tissue contact, facilitates cleaning, and reduces plaque accumulation. Case report: A 23-year-old male patient lost his mandibular right first molar and sought to restore chewing function. After clinical and radiographic examinations, it was decided to restore the edentulous area of tooth 46 using a PFM bridge with a sanitary pontic design. Teeth 45 and 47 underwent abutment preparation, impressions, and fabrication of the bridge. Discussion: The sanitary pontic design has been shown to facilitate oral hygiene, especially under the pontic. The space between the pontic and the alveolar mucosa facilitates effective brushing or flossing, reducing plaque and the risk of gingival inflammation. PFM materials provide appropriate strength and durability for posterior restorations. Conclusion: A Porcelain Fused Metal (PFM) bridge with a sanitary pontic design is an effective restorative alternative for posterior tooth loss, improving hygiene and supporting long-term periodontal health.